Legalitas Perkawinan Akibat Kehamilan di Luar Nikah Serta Implikasinya Terhadap Status Anak - Nina Handayani; Novita Eka Wardhani; Nayla Oktri Ramadhani; Afrilia Era Vazira; Citra Bethari Ratih; Baidhowi (CV. ITTC INDONESIA, 2025)
Pregnancy outside of marriage is a social phenomenon that raises legal, moral, and religious issues. From an Islamic legal perspective, pregnancy resulting from adultery is considered a major sin, but Islam still provides room for repentance and protection of dignity for women who experience it. In Indonesia, cases of pregnancy outside of marriage are often resolved through marriage, but the legal status of such marriages and the status of the children born from them often cause debate. This study applies a normative-descriptive method with a literature review approach that refers to laws and regulations, fatwas (religious edicts) issued by Islamic scholars, Constitutional Court decisions, and various relevant academic studies. The results of the study show that according to Islamic law, women who become pregnant outside of marriage still have the right to marry, either to the man who impregnated them or to another party who is willing to take responsibility. However, the child's lineage remains with the mother. In the Indonesian positive legal system, Article 43 paragraph (1) of Law Number 1 of 1974, reinforced by Constitutional Court Decision Number 46/PUU-VIII/2010, stipulates that children born outside of marriage have a civil relationship with their mother and biological father, provided that the relationship can be proven through scientific means. Thus, both Islamic law and national law emphasize the importance of protecting women and children born out of wedlock through legal means.